Mediating role of social support between sleep quality, anxiety and depressive symptoms in Chinese women undergoing in vitro fertilization treatment. (June 2020) - Cui, Ying; Li, Danian; Zhou, Borong; Lin, Yanshan; Zeng, Yingchun
Introduction: Infertility is a significant health problem, and the prevalence of infertility among women is increasing in developing countries. This study aims to explore whether social support plays a mediating role in the links between exogenous variables, sleep quality, anxiety, and depressive symptoms in Chinese women undergoing in vitro fertilization. Methods: This is a cross-sectional study comprising a sample of Chinese women undergoing in vitro fertilization treatment at a tertiary reproductive medicine center located in South China. Results: The final testing model showed good fit, with normed χ 2 = 39.317, p = 0.055, comparative fit index = 0.948, Tucker–Lewis index = 0.902, incremental fit index = 0.951, normed fit index = 0.906, root mean square error of approximation = 0.046). The final path model supported the proposed model: partner relationship, a woman's age, financial strain, duration of infertility, and cycles of in vitro fertilization were exogenous variables for depressive symptoms, while social support was a significant mediator between sleep quality, anxiety, and depressive symptoms. Conclusion: The empirical support from this study could facilitate the development of appropriate interventions to reduce depressive symptoms, and to promote the mental health of Chinese women undergoing in vitro fertilization treatment.